Life Writing and Rural Queer Studies: Queerying the Spatialisation of Modern Sexual Identities in Australia and Six Hundred Something Kilometres - Anderson, Jay Lachlin (Curtin University, 2020)
This research thesis explores significant criticisms levelled by academics of rural queer studies— the spacialisation of modern LGBTIQ+ identity, politics and academia and a metronormative narrative that (re)produces it. Through the practice-led research methodology of Dallas Baker’s “queer life writing,” I argue that creative writing can resist the demands of metronormativity by employing what Scott Herring refers to as a “rural stylistics” and attempt to provide examples of contemporary Australian writers who have done so.